2023
DOI: 10.3389/fcimb.2023.1142199
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics of respiratory viruses in hospitalized children during the COVID-19 pandemic in southwestern China

Abstract: BackgroundMultinational studies have reported that the implementation of nonpharmaceutical interventions (NPIs) to control severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission coincided with the decline of other respiratory viruses, such as influenza viruses and respiratory syncytial virus.ObjectiveTo investigate the prevalence of common respiratory viruses during the coronavirus disease 2019 (COVID-19) pandemic.MethodsRespiratory specimens of children with lower respiratory tract infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Firstly, our study indicated that the infection rate of LRTIs was observed to be higher in boys than in girls ( Table 1 ; Figure 1 ), a trend possibly linked to the demographic composition of children in Xiangtan. This finding aligns with domestic investigations ( 23 , 24 ). Compared to 2018–2019, the incidence of LRTIs decreased significantly in 2020–2021, but pathogen positivity and single pathogen positivity increased over the same period, this observation may be attributed to the preventive measures implemented for COVID-19 pandemic ( Table 2 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Firstly, our study indicated that the infection rate of LRTIs was observed to be higher in boys than in girls ( Table 1 ; Figure 1 ), a trend possibly linked to the demographic composition of children in Xiangtan. This finding aligns with domestic investigations ( 23 , 24 ). Compared to 2018–2019, the incidence of LRTIs decreased significantly in 2020–2021, but pathogen positivity and single pathogen positivity increased over the same period, this observation may be attributed to the preventive measures implemented for COVID-19 pandemic ( Table 2 ).…”
Section: Discussionsupporting
confidence: 93%
“…Overall, pathogenetic studies conducted before and after COVID-19 not only contribute to a more accurate medical basis for clinical diagnosis and treatment, and evidence-based medicine, but also enhance healthcare professionals' comprehension of regional respiratory infection characteristics caused by common pathogens. The study acknowledges limitations such as not testing for other common or rare respiratory pathogens in children such as HRV, Chlamydia and HMPV, and not testing for different subtypes of common viruses, thus not reflecting the epidemiological status of these pathogens (20)(21)(22)(23)(24)(25)(26). To enhance the surveillance of respiratory pathogens in children, more comprehensive multiplex assays are needed to monitor LRTIs for common respiratory pathogens as well as infections with different viral subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, an obvious resurgence was absent in the first quarter of 2020 and the fourth quarters of 2019 and 2022, suggesting a potential peak delayed to 2023. The effects of strict NPIs against COVID-19 may have contributed to alterations in the seasonal patterns of viral infections in other Chinese populations as well 37 , 38 . Typical seasonal patterns were also observed in the number of S. aureus isolates resistant to penicillin, erythromycin, and clindamycin in 2018, 2019, and 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Coinfections with multiple respiratory viruses are uncommon, and whether they can complicate the clinical course and management of affected individuals is not well described. Moreover, underlying comorbidities, such as diabetes and hypertension, or unhealthy habits, such as smoking, can increase the risk of severe illness and complications ( 2 , 10 ).…”
Section: Introductionmentioning
confidence: 99%